1996
DOI: 10.1021/ma951642n
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion Polymerization of Styrene in Supercritical Carbon Dioxide:  Importance of Effective Surfactants

Abstract: The dispersion polymerization of styrene in supercritical CO2 using amphiphilic diblock copolymers to impart steric stabilization was investigated. Lipophilic, CO2-insoluble materials can be effectively emulsified in carbon dioxide using amphiphilic diblock copolymer surfactants. The resulting high yield (>90%) of polystyrene is obtained in the form of a stable polymer colloid comprised of submicron-sized particles. The particle diameter and distribution of sizes were shown to be dependent on the nature of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
190
0
2

Year Published

1998
1998
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 211 publications
(200 citation statements)
references
References 22 publications
8
190
0
2
Order By: Relevance
“…Thus, living polymer was isolated without the usual work up using organic solvents, which is significant from an experimental and environmental perspective. This represented the first time precipitation polymerizations of S had been taken to high conversion, since Canelas and DeSimone had reported low conversions for conventional radical precipitation polymerizations (20% S loading) in scCO 2 at 65 C over 24 h. 71,72 However, we found that the conventional radical precipitation polymerization of S (40% w/v) in scCO 2 at higher temperature (110 C) could give high conversions (80%), 21 thus suggesting the important factor is temperature rather than the controlled/living nature of the polymerization.…”
Section: Precipitation Clrp In Supercritical Comentioning
confidence: 81%
See 2 more Smart Citations
“…Thus, living polymer was isolated without the usual work up using organic solvents, which is significant from an experimental and environmental perspective. This represented the first time precipitation polymerizations of S had been taken to high conversion, since Canelas and DeSimone had reported low conversions for conventional radical precipitation polymerizations (20% S loading) in scCO 2 at 65 C over 24 h. 71,72 However, we found that the conventional radical precipitation polymerization of S (40% w/v) in scCO 2 at higher temperature (110 C) could give high conversions (80%), 21 thus suggesting the important factor is temperature rather than the controlled/living nature of the polymerization.…”
Section: Precipitation Clrp In Supercritical Comentioning
confidence: 81%
“…2,70 There is a general lack of CO 2 -soluble polymers, and the polymeric stabilizers normally used are diblock copolymers comprising a CO 2 -philic segment which is almost always a siloxane or fluorocarbon, and a CO 2 -phobic segment to interact with the polymer particle. 2,[71][72][73][74][75] Random copolymers containing a fluorinated acrylate have also been used with success, 76 as well as ionic hydrocarbon surfactants containing CO 2 -philic PVAc units. 77 The high cost of fluorinated colloidal stabilizers has led to a tendency towards the use of cheaper siloxane-based alternatives.…”
Section: As Polymerization Mediummentioning
confidence: 99%
See 1 more Smart Citation
“…The next study of MMA dispersion polymerizations focused on the use of another class of surfactants, based on poly(dimethyl siloxane) (PDMS), which are less expensive than fluoropolymer-based surfactants [24]. Initial attempts of styrene dispersion polymerizations in CO 2 with PFOA and PDMS homopolymer stabilizers gave low yields and latex instability, but the block copolymers PS-b-PFOA and PS-b-PDMS produced submicron-sized PS particles [25,26]. Block copolymer surfactants containing poly(vinyl acetate) (PVAc), PVAc-b-PDMS and PVAc-b-PFOA, were effective stabilizers for dispersion polymerizations of vinyl acetate and copolymerizations of vinyl acetate and ethylene [27].…”
Section: Dispersion Polymersmentioning
confidence: 99%
“…Recently, PFOA and its methacrylate analog PFOMA were found to be effective stabilizers for PS at higher CO 2 pressures (370 bar) [28] while PFOA was ineffective at lower pressures of 204 bar [25]. Random copolymers, PS-co-PFOMA and PS-co-TMSOSPMA (3-[tris(trimethylsilyloxy)silyl]propyl methacrylate), are also effective stabilizers, producing micron-sized PS particles [29].…”
Section: Dispersion Polymersmentioning
confidence: 99%